Chronic Kidney Disease: A Case Series (Part 7) (Advancements in Homeopathic Research, 2025)
In their previous series of six publications, Gupta  et. al. demonstrated that patients of chronic kidney  disease (CKD) and acute renal failure (ARF)  can be successfully managed by homoeopathic  medicines. This seventh case series is on successful  management of CKD patients by maintaining their  serum creatinine level and eGFR within a reasonable  range, delaying further deterioration and improving  their quality of life for a considerable period of time  without haemodialysis. The first case in this series  is of 68-year old hypertensive male suffering from  chronic renal failure with follow up of about 4 years.  His S. Creatinine, Urea level reduced gradually and  became normal with homoeopathic treatment without  dialysis. His eGFR also increased and he became  clinically asymptomatic. The second case is of a 42- year old hypertensive, nondiabetic female. Her S.  creatinine and eGFR was maintained for more than 3  years. The third patient is a 55-year old hypertensive,  nondiabetic, anaemic female. Her S. Creatinine  and S. Urea gradually reduced and eGFR improved  with homoeopathic treatment without dialysis. Her  treatment is still continued.
Keywords: Haemodialysis (HD); peritoneal dialysis (PD); chronic kidney disease (CKD); chronic renal failure (CRF); end stage renal disease (ESRD); serum urea; blood urea nitrogen (BUN); serum creatinine; estimated glomerular filtration rate (eGFR); renal transplant; homoeopathic treatment